2021
DOI: 10.51847/de0asem506
|View full text |Cite
|
Sign up to set email alerts
|

National Survey: Knowledge, Attitude and Practice Towards COVID-19 among Iraqi Pharmacy Students

Abstract: The recent infection by the COVID-19 virus has rapidly become a major health concern, both in terms of its strong impact on the health system, and economical burden. Assessment of pharmacy students' level of awareness, attitude, and knowledge about the recent COVID-19 infection in Iraq. A population-based cross-sectional study that involved pharmacy college students across the country, this study used an electronic-based questionnaire that was delivered to each of the participants online. The study included 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In Ethiopia, Pearson reported that as many as 15% of patients with MH lepromatous experience a dapsone resistance relapse. When tested on these Ethiopian strains on mice, unlike in other regions, the majority had resistance to 0.0001% dapsone in mice and not to a higher degree [16]. In conclusion, the findings of the prevalence of relapses of secondary dapsone resistance were not high.…”
Section: Research About Chemoprohpylaxis Drugs Dapsonmentioning
confidence: 65%
See 1 more Smart Citation
“…In Ethiopia, Pearson reported that as many as 15% of patients with MH lepromatous experience a dapsone resistance relapse. When tested on these Ethiopian strains on mice, unlike in other regions, the majority had resistance to 0.0001% dapsone in mice and not to a higher degree [16]. In conclusion, the findings of the prevalence of relapses of secondary dapsone resistance were not high.…”
Section: Research About Chemoprohpylaxis Drugs Dapsonmentioning
confidence: 65%
“…Numerous studies have shown that the accumulation of clofazimine in macrophages, the site of Mycobacterium leprae, causes the local emergence of superoxide and hydroxyl radicals. These products are inhibitors of the multiplication of Mycobacterium leprae [16]. This drug acts as an anti-inflammatory which may benefit type 2 reactions.…”
Section: Chlofaziminementioning
confidence: 99%
“…Health promotion programs carried out by pharmacy students impact increasing public knowledge and good perceptions, extending the role of pharmacists in ways that are beneficial to the communities where they work [28,29]. By providing continuous education involving apothecary and all health workers, it is expected that the community who has a better level of understanding has a positive and optimistic perception of controlling the COVID-19 pandemic [30,31].…”
Section: Resultsmentioning
confidence: 99%